Inducible and constitutive heat shock gene expression responds to modification of Hsp70 copy number in Drosophila melanogaster but does not compensate for loss of thermotolerance in Hsp70 null flies - Bettencourt, Brian R (BioMed Central, 2008)
BACKGROUND: The heat shock protein Hsp70 promotes inducible thermotolerance in nearly every organism examined to date. Hsp70 interacts with a network of other stress-response proteins, and dissecting the relative roles of these interactions in causing thermotolerance remains difficult. Here we examine the effect of Hsp70 gene copy number modification on thermotolerance and the expression of multiple stress-response genes in Drosophila melanogaster, to determine which genes may represent mechanisms of stress tolerance independent of Hsp70. RESULTS: Hsp70 copy number in four strains is positively associated with Hsp70 expression and inducible thermotolerance of severe heat shock. When assayed at carefully chosen temperatures, Hsp70 null flies are almost entirely deficient in thermotolerance. In contrast to expectations, increasing Hsp70 expression levels induced by thermal pretreatment are associated with increasing levels of seven other inducible Hsps across strains. In addition, complete Hsp70 loss causes upregulation of the inducible Hsps and six constitutive stress-response genes following severe heat shocks. CONCLUSION: Modification of Hsp70 copy number quantitatively and qualitatively affects the expression of multiple other stress-response genes. A positive association between absolute expression levels of Hsp70 and other Hsps after thermal pretreatment suggests novel regulatory mechanisms. Severe heat shocks induce both novel gene expression patterns and almost total mortality in the Hsp70 null strain: alteration of gene expression in this strain does not compensate for Hsp70 loss but suggests candidates for overexpression studies.